UPAYA PENDIDIKAN LIFE SKILL DALAM MENUMBUHKAN KEWIRAUSAHAAN WARGA BELAJAR PAKET C - Ricky Muhamad Reza; Nandang Rukanda; Prita Kartika (Comm-Edu (Community Education Journal), 2022)
Residents of learning package c in addition to requiring academic knowledge and provision of skills relevant to their living environment so that residents studying package c can immediately work according to the skills they can have while attending education which is called life skills education or life skills education in PKBM Girisewu District  Cisewu. The purpose of this research is to describe the efforts of life skills education in growing entrepreneurship for learning citizens package c.  The method used in this study is a qualitative descriptive method, using data collection techniques by means of observation and interviews. The research subjects are one manager, one tutor and three study residents PKBM Girisewu.  The results show that growing entrepreneurship is formed from life skills education with the planning used in growing entrepreneurship through life skills education, the positive impact for residents learning package c following life skills education is that learning citizens are able to analyze entrepreneurial opportunities and take advantage of the potential around them as entrepreneurial commodities in the form of  goods or services. The conclusion is that the role of PKBM is very supportive in community empowerment through PKBM's flagship program, namely life skills education programs that help improve the community's economy.